Design, manufacturing and performance OF Fe–Mn–Si–Ni–Cr shape memory seamless couplings - Esquivel, Isidro Gabriel (2021)
The Fe–Mn–Si shape memory (SM) alloys have attracted a great deal of interest due to their good technological characteristics and mechanical properties, combined with the SM effect. They are especially useful for applications like shaft and pipe couplings. In this work, we present the development and evaluation of a procedure to manufacture SM seamless couplings. After analysing industrial forming methods, we designed and fabricated a prototype of a punch-extrusion (PE) die and obtained seamless tubes of satisfactory quality and length for manufacturing couplings. Finally, we measured the performance and SM properties of the PE couplings and compared these characteristics to those of couplings machined from a cast ingot. We concluded that a multi-step processing is an efficient solution that mitigated problems resulting from billet cooling during punching because it allows the alloy to be reheated. The PE couplings that were diametrically expanded 4% and annealed at 700 °C exhibited 75% shape recovery, while the control samples showed 20% less recovery. The union of 21 mm diameter shafts by means of PE couplings annealed at 700 °C showed 40 N-m/cm2 normalized torque transmission, which was 25% greater than that found for the cast ingot couplings. We also analyzed the advantages of the PE couplings compared to a traditional shrink-fit connection.